Tendances et perspectives de l'agriculture et de l'elevage en Afrique tropicale - Montgolfier-Kouevi, C. de; Vlavonou, A. (CIPEA, 1981)
Evaluates resources existing in tropical Africa on a regional and zonal basis, and analyses demand and supply projections of agricultural and food products up to the year 2000. Discusses the effects of the energy crises on agriculture in developed and developing countries, and the development potential of the livestock sector over the next 20 years considering the supporting capacity of the land as well as the farm inputs required to meet development targets. Presents the role of livestock as a farm input providing manure and traction, and the potential of hides and skins; with annex on the new energy strategies.